Review of software applications for agricultural production in Croatia - Brezinščak, Luka (Array, 2019)
The application of mobile devices (smartphones, tablets, etc.) to the agriculture sector has been greatly increased in the last decade. The ICT technologies have become an essential part of any business. Using Internet on mobile devices can prove to be essential in agriculture production. A new generation of mobile devices are lower in price and more user-friendly. This paper provides an overview of software applications that are created in Croatia and are mostly in the Croatian language. They are divided into groups of agriculture related applications; agriculture management information apps; agriculture information resource apps; agriculture calculator apps; agriculture news apps, weather apps. The research shows the agri-apps are still in its infancy and we can say that it reflects the state of agriculture in Croatia. Apps are a promising solution for farmers enabling them quick and trustworthy access to information. At the moment, further analyses are needed for scientific proof and improvement of a product.